Brain penetration and efficacy of tepotinib in orthotopic patient-derived xenograft models of MET-driven non-small cell lung cancer brain metastases. (January 2022) - Friese-Hamim, Manja; Clark, Anderson; Perrin, Dominique; Crowley, Lindsey; Reusch, Christof; Bogatyrova, Olga; Zhang, Hong; Crandall, Timothy; Lin, Jing; Ma, Jianguo; Bachner, David; Schmidt, Jürgen; et al.
Highlights: The selective MET inhibitor tepotinib penetrated the intact rat blood–brain barrier. Tepotinib activity was tested in NSCLC brain metastasis patient-derived xenografts. Of 20 screened subcutaneous models, two were sensitive to tepotinib. Both sensitive models had high-level MET amplification (copy number: 11.2 and 24.2). Tepotinib led to marked regression of both models after orthotopic implantation. Abstract: Central nervous system-penetrant therapies with intracranial efficacy against non-small cell lung cancer (NSCLC) brain metastases are urgently needed. We report preclinical studies investigating brain penetration and intracranial activity of the MET inhibitor tepotinib. After intravenous infusion of tepotinib in Wistar rats (n = 3), mean (±standard deviation) total tepotinib concentration was 2.87-fold higher in brain (505 ± 22 ng/g) than plasma (177 ± 20 ng/mL). In equilibrium dialysis experiments performed in triplicate, mean tepotinib unbound fraction was 0.35% at 0.3 and 3.0 µM tepotinib in rat brain tissue, and 4.0% at 0.3 and 1.0 µM tepotinib in rat plasma. The calculated unbound brain-to-plasma ratio was 0.25, indicating brain penetration sufficient for intracranial target inhibition. Of 20 screened subcutaneous patient-derived xenograft (PDX) models from lung cancer brain metastases (n = 1), two NSCLC brain metastases models (LU5349 and LU5406) were sensitive to the suboptimal dose of tepotinib of 30 mg/kg/qd (tumor volume change [%TV]: –12% and –88%, respectively). Molecular profiling (nCounter®; NanoString) revealed high-level MET amplification in both tumors (mean MET gene copy number: 11.2 and 24.2, respectively). Tepotinib sensitivity was confirmed for both subcutaneous models at a clinically relevant dose (125 mg/kg/qd; n = 5). LU5349 and LU5406 were orthotopically implanted into brains of mice and monitored by magnetic resonance imaging (MRI). Tepotinib 125 mg/kg/qd induced pronounced tumor regression, including complete or near-complete regressions, compared with vehicle in both orthotopic models (n = 10; median %TV: LU5349, –84%; LU5406, –63%). Intracranial antitumor activity of tepotinib did not appear to correlate with blood–brain barrier leakiness assessed in T1-weighted gadolinium contrast-enhanced MRI.